116k views
1 vote
Helllpp plzzzzzzzzzz

Helllpp plzzzzzzzzzz-example-1
User Roy Shoa
by
5.7k points

2 Answers

4 votes

Answer:


-2b-1

Explanation:


3r+2-r=-4b


2r+2=-4b (Subtract r from 3r)


2r+2-2=-4b-2 (Subtract 2 from both sides)


(2r)/(2) = (-2b-1)/(2) (Divide both sides by 2)


r=-2b-1

User Suyash Chavan
by
4.4k points
3 votes

Answer: Choice C) -2b - 1

=================================================

Work Shown:

3r + 2 - r = -4b

(3r-r) + 2 = -4b

2r + 2 = -4b

2r+2-2 = -4b-2 .... subtracting 2 from both sides

2r = -4b-2

2r/2 = (-4b-2)/2 .... dividing both sides by 2

r = (-4b-2)/2

r = (-4b)/2 - 2/2 ... break up the fraction

r = -2b - 1

User Muneef M
by
5.0k points